COORDINATION AND CONTROL OF USE OF RESOURCES IN A MEDICALFACILITY - Petkova, Ivelina (E-Journal VFU, 2024)
In recent years, medical facilities providing health services to the population havebeen the subject of a wide public discussion regarding the status and efficiency of theresources used.This article aims to highlight characteristic features and specifics in the construction,coordination and control of the resources used in medical facilities.
Keywords: resources; medical facilities; control